2018
DOI: 10.1007/s10545-018-0223-y
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term complications of glycogen storage disease type Ia in the canine model treated with gene replacement therapy

Abstract: Here, we show that the canine GSD Ia model demonstrates similar long-term complications as GSD Ia patients in spite of gene replacement therapy. Further development of gene therapy is needed to develop a more effective treatment to prevent long-term complications of GSD Ia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 64 publications
(80 reference statements)
0
31
0
Order By: Relevance
“…The GSD Ia canine model provides an outbred genetic model for the study of complications of GSD Ia (34). Three age-matched, male GSD Ia dogs were sustained by adeno-associated virus (AAV) vector-mediated gene therapy as described (35), which partially reversed biochemical abnormalities without preventing the long-term risk for HCA and HCC (36). Ultrasound examination following 1.2, 2.4 and 3.6 months of bezafibrate treatment revealed a more homogenous appearance of the liver after treatment, in comparison with baseline ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GSD Ia canine model provides an outbred genetic model for the study of complications of GSD Ia (34). Three age-matched, male GSD Ia dogs were sustained by adeno-associated virus (AAV) vector-mediated gene therapy as described (35), which partially reversed biochemical abnormalities without preventing the long-term risk for HCA and HCC (36). Ultrasound examination following 1.2, 2.4 and 3.6 months of bezafibrate treatment revealed a more homogenous appearance of the liver after treatment, in comparison with baseline ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The animal models of GSD Ia require gene therapy to promote long-term survival, including both the homozygous G6pc−/− mouse or naturally occurring canine models (40). While G6pc−/− mice were used to evaluate the short-term benefits of bezafibrate, we employed the canine model for GSD Ia to study longterm effects of GSD Ia, including the known occurrence of HCA and HCC (36). Of note, gene therapy cannot prevent these tumors from developing because of the transient nature of AAV vectormediated gene therapy (41).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated glycogen was remarkably decreased in the liver of dogs with GSD Ia, in association with decreased hepatic lipids, following administration of an AAV serotype 2 vector cross-packaged as AAV serotype 8 (AAV2/8-G6Pase), and efficacy was maintained for 1 year 15 . We recently described five GSD Ia dogs treated with AAV-G6Pase therapy that survived up to 8 years; however, four of these dogs had hepatocellular tumors, indicating some loss of therapeutic efficacy 16 …”
Section: Introductionmentioning
confidence: 99%
“…Our group recently published a very similar gene therapy study, but the GSD Ia dogs were maintained on a more typical diet of only three feedings per day (Brooks et al 2018). However, 4/5 AAV vector-treated dogs developed hepatocellular adenomas and carcinoma and 3/5 developed chronic kidney disease.…”
mentioning
confidence: 99%
“…The kidney sparing in Lee et al can be attributed to intensive dietary therapy (Lee et al 2018). Brooks et al reported tubule-interstitial lesions and glomerular changes in the older GSD Ia dog cohort treated with AAV vectors (Brooks et al 2018). …”
mentioning
confidence: 99%